“The Banality of Evil” and Culpability in Criminal Law - Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
In the first part of this scientific work the author discusses evil as an anthropological phenomenon. For the purposes of the work he differentiates instrumental and ideological evil. However, actors exist who do not fit into these typical forms. The author stresses that the twentieth century has given rise to a special kind of evil, which may be referred to as banal evil.The author conducts the analysis of this type of evil by analyzing the personality and work of Adolf Eichmann, as its typical literary representative. Examining critically the court process and reasons for his sentence, as well as the opinions of those present at the trial against Eichmann, the author, in the central part of the work, attempts to define the subject phenomenon.In the final part of the work the author examines the question of Eichmann’s culpability for the committed crimes. He controverts the opinions of certain authors that Eichmann, but also other typical representatives of banal evil, could not have been conscious that they are doing something forbidden, and explains in detail why the position should be accepted that they have acted with premeditation.
Keywords: evil, the banality of evil, culpability, criminal law.